Perbandingan Usability Learning Management System Edmodo dan Google Classroom Menggunakan Heuristic Walkthrough (Studi Kasus: SMKN 11 Malang) - Sabhian Bagaspati Susilo; Satrio Hadi Wijoyo; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The implementation of the Learning Management System (LMS) in Malang Vocational High School has encountered many problems in the display that is difficult to understand, users do not understand the features of the system so that problems arise in the aspects of Usability and Learnability. Because the teacher has difficulty choosing which LMS is good to use, the researcher evaluated the comparisons of the two LMSs used namely Edmodo and Google Classroom using the Heuristic Walkthrough which is a combination of two methods namely Heuristic Evaluation on Usability and Cognitive Walkthrough on Learnability. The respondents involved were four experts and five teachers in each LMS. The results of the study show that the Learnability factor Edmodo has a total of 14 problems and two 21 for the Google Classroom. In Usability results, Edmodo has 23 problems and has an average severity rating of 2.5 while Google Classroom has 9 problems and has an average severity rating of 2.7. From these results, Edmodo is recommended for new users because it excels in Learnability aspects while Google Classroom is recommended by experts because it excels in Usability.